A systematic review of the use of simulation and reflection as summative assessment tools to evaluate student outcomes following interprofessional education activities. Issue 6 (2nd November 2022) - El-Awaisi, Alla; Jaam, Myriam; Wilby, Kyle John; Wilbur, Kerry
ABSTRACT: Despite the increasing emphasis on interprofessional education (IPE) in curricula and the potential benefits for student learning, there appears to be a lack of evidence directing authentic and accurate assessment of student-learning outcomes and translation of assessment data into scores and grades. Given the increasing importance of reflection and simulation in IPE, the purpose of this systematic review was to identify, appraise, and synthesize published literature using reflection and simulation as summative assessment tools to evaluate student outcomes following IPE activities. The Crowe Critical Appraisal Tool was used to appraise the included articles for quality. This systematic review yielded only five studies of marginal quality that could highlight the limited rigorous use of either reflection or simulation for summative assessment purposes. This review has identified a need for summative IPE assessment alongside formative assessments. Furthermore, training needs to be offered to both faculty assessors, to ensure they are competent and results are reproducible, and students, to equip them with the knowledge, critical thinking skills, and attitude for becoming reflective practitioners who are able to practice interprofessionally. The assessment of IPE remains a challenge, and there is a clear gap in the literature where research needs to grow.